[tex]\displaystyle\bf\\\frac{47^{2} -3^{2} }{27^{2} +2\cdot 27\cdot 23+23^{2} } =\frac{(47-3)\cdot(47+3)}{(27+23)^{2} } =\\\\\\=\frac{44\cdot 50}{50^{2} } =\frac{44}{50} =0,88[/tex]
При решении были применены формулы .
[tex]\displaystyle\bf\\1) \ a^{2} - b^{2} =(a-b)\cdot(a+b)\\\\\\2)\\\\a^{2} +2\cdot a \ \cdot b+b^{2} =(a+b)^{2}[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
[tex]\displaystyle\bf\\\frac{47^{2} -3^{2} }{27^{2} +2\cdot 27\cdot 23+23^{2} } =\frac{(47-3)\cdot(47+3)}{(27+23)^{2} } =\\\\\\=\frac{44\cdot 50}{50^{2} } =\frac{44}{50} =0,88[/tex]
При решении были применены формулы .
[tex]\displaystyle\bf\\1) \ a^{2} - b^{2} =(a-b)\cdot(a+b)\\\\\\2)\\\\a^{2} +2\cdot a \ \cdot b+b^{2} =(a+b)^{2}[/tex]